Labour Markets in Low-Income Countries Challenges and Opportunities - Lam, David (Oxford University Press, 2021)
Employment and job creation are key components in achieving economic growth and sustainable development, particularly in low-income countries. The growing size of the working-age population in many developing regions underscores the need to further strengthen labour market structures in the world's poorest countries. Despite the importance of studying emerging labour markets, and investigating which policies are more successful, the evidence is rather limited. Against this backdrop, the joint IZA/FCDO Growth and Labour Markets in Low Income Countries (GLM|LIC) programme was established and has taken important steps to close this gap. Covering topics such as poverty, informality and rural labour, skills training and behaviour, gender inequality, youth and child labour, and migration, this volume presents key takeaways from most recent research in the field. Which development policies will work, which strategies will fail? The authors provide an in-depth discussion of current development programmes, based on the results of new evaluation studies, and derive important policy lessons.